ABOUT FUNCTIONAL DIAGNOSTICS OF CARS WITH AN ELECTRIC POWER PLANT - Anton S. Chernyshkov; Alexander I. Fedotov; Oleg S. Yan’kov (International Journal of Advanced Studies, 2023)
The article is devoted to the development of a method of functional diagnostics of cars with an electric power plant on stands with running drums. The necessity of carrying out functional diagnostics of cars with an electric power plant is analyzed. The reasons hindering the development and implementation of the bench method for monitoring the technical condition of cars with an electric power plant are considered. The article presents the results obtained by the authors in previous works. The developed mathematical models are presented, test modes for testing cars with an electric power plant on a stand with running drums are proposed. The results of analytical and experimental identification of interrelations between the parameters of the technical condition of a car with an electric power plant and the main parameters of its functioning are presented. The revealed patterns made it possible to develop a method of functional diagnostics of cars with an electric power plant based on the use of a diagnostic matrix. The developed method of functional diagnostics is implemented by measuring and then comparing with the normative values of the main parameters of the functioning of a car with an electric power plant when monitoring its technical condition on a stand with running drums. A control algorithm is proposed that allows implementing the developed method of functional diagnostics.